1997
DOI: 10.1038/bjc.1997.309
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro biotransformation of the lithium salt of gamma-linolenic acid by three human carcinomas

Abstract: Summary Lipid metabolism has been considered recently as a novel target for cancer therapy. In this field, lithium gamma-linolenate (LiGLA) is a promising experimental compound for use in the treatment of human tumours. In. vivo and in vitro studies allowed us to assess the metabolism of radiolabelled LiGLA by tumour tissue and different organs of the host. In vitro studies demonstrated that human pancreatic (AsPC-1), prostatic (PC-3) and mammary carcinoma (ZR-75-1) cells were capable of elongating GLA from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The sizes of the transcripts at 4.3 kb and 3.1 kb, respectively, agree well with those reported earlier in human tissues [4^6]. Our ¢ndings in Chang cells showing the lack of v-6 Table 4 Percent of radioactivity recovered in n-3 and other fatty acids of Chang and ZR-75-1 cells after a 12 h incubation with [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Values are the mean þ S.D. of at least three determinations.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The sizes of the transcripts at 4.3 kb and 3.1 kb, respectively, agree well with those reported earlier in human tissues [4^6]. Our ¢ndings in Chang cells showing the lack of v-6 Table 4 Percent of radioactivity recovered in n-3 and other fatty acids of Chang and ZR-75-1 cells after a 12 h incubation with [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Values are the mean þ S.D. of at least three determinations.…”
Section: Discussionsupporting
confidence: 87%
“…ND: not detected. Table 5 Percent of radioactivity recovered in n-6 desaturation and elongation metabolites of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] desaturase activity for any substrate and a corresponding absence of mRNA, but, with signi¢cant v-5 desaturase activity and its mRNA, are the ¢rst to suggest that v-5 and v-6 desaturase genes have, at least in part, independent control mechanisms. However, our data are not su¤cient to distinguish between direct transcriptional control or RNA transcript stability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that of all the fatty acids tested, GLA or DGLA was the most effective in selectively killing the tumor cells [ 6 ]. In a co-culture experiment wherein normal human skin fibroblasts and human breast cancer cells were grown together in a petri dish supplemented with GLA or DGLA, only human breast cancer cells were eliminated without any effect on normal skin fibroblasts [ 65 , 68 , 70 , 71 ]. These results reconfirmed that GLA or DGLA show selective tumoricidal action at least in vitro.…”
Section: Efficacy Of Dgla Against Tumorsmentioning
confidence: 99%
“…Topically applied GLA is an effective agent against superficial bladder carcinoma whereas the novel compound meglumine-GLA synergistically enhanced the cytotoxicity of epirubicin toward human urothelial carcinoma cell lines (70). Encouraging data were also obtained with the lithium salt of GLA in a phase III study on pancreatic cancer patients (71,72). A propane diol GLA/EPA emulsion provided a 640fold higher dose of both GLA and EPA as compared with free PUFA.…”
Section: Fa Therapies For Specific Health Concernsmentioning
confidence: 98%